ANALYSIS OF TAX REVENUES MOBILIZATION IN NORTH CAUCASIAN FEDERAL DISTRICT’S REGIONS BASED ON EFFECTIVE TAX RATE INDICATOR - Yelena Mikhailovna Dzhurbina; Dmitry Ivanovich Fateyev (Современная наука и инновации)
The article is devoted to research of tax revenues mobilization specificity in grant dependent subjects of North Caucasian federal district with the help of the effective tax rates toolkit, allowed to reveal «failures» in efficiency of separate fiscal forms administration and to determine the directions of their reserves implementation.